2001
DOI: 10.1038/sj.neo.7900175
|View full text |Cite
|
Sign up to set email alerts
|

Blocking CHK1 Expression Induces Apoptosis and Abrogates the G2 Checkpoint Mechanism

Abstract: Checkpoint kinase 1 (Chk1) is a checkpoint gene that is activated after DNA damage. It phosphorylates and inactivates the Cdc2 activating phosphatase Cdc25C. This in turn inactivates Cdc2, which leads to G2/M arrest. We report that blocking Chk1 expression by antisense or ribozymes in mammalian cells induces apoptosis and interferes with the G2/M arrest induced by adriamycin. The Chk1 inhibitor UCN-01 also blocks the G2 arrest after DNA damage and renders cells more susceptible to adriamycin. These results ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 36 publications
3
27
0
Order By: Relevance
“…Inhibition of Chk1 in the absence of the DNA-damaging agent increased cell death in all cell lines indicating that Chk1 played also a role in survival of MM cells. This finding is in agreement with a previous report documenting the induction of apoptosis in H1299 cells by Chk1 anti-sense 20 although other studies observed no increase of apoptotic cells after siRNA treatment.…”
Section: Discussionsupporting
confidence: 83%
“…Inhibition of Chk1 in the absence of the DNA-damaging agent increased cell death in all cell lines indicating that Chk1 played also a role in survival of MM cells. This finding is in agreement with a previous report documenting the induction of apoptosis in H1299 cells by Chk1 anti-sense 20 although other studies observed no increase of apoptotic cells after siRNA treatment.…”
Section: Discussionsupporting
confidence: 83%
“…24,54 Furthermore, downregulation of Chk1 using anti-sense and ribozyme approaches also caused significant cell death in the absence of DNA damage in mammalian cells. 55 However, other studies indicate that Chk1 inhibition might not be lethal in mammalian cells. It was shown that Chk1 downregulation abrogated radiation-induced S and G 2 checkpoints 56,57 but had no significant effect on cell death.…”
Section: Discussionmentioning
confidence: 99%
“…30 Here, we show in mouse oocytes that Chk1 is expressed from GV to MII stages. These data indicate that Chk1 may play a role not only in mitosis, but also in meiosis.…”
Section: Discussionmentioning
confidence: 99%